GENDER JUSTICE AND CULTURAL DIMENSION OF RELIGION, A PROPOSAL TO APPLY THE PROPHETIC TRADITION (THE HADITH) IN PROMOTING GENDER JUSTICE AMONG INDONESIAN MUSLIMS - Faqihuddin Abdul Kodir (Universitas Gadjah Mada, 2011)
By arguing that religion as interpretative culture of people in their context, suggested by Clifford Geertz, this paper proposes an interpretation-oriented approach to the texts of the hadith of the Prophet Muhammad rather than a critical-deconstructive approach. The interpretation-oriented approach focuses on positive reading towards the hadith that advocates issues of gender justice; whether through selecting classical methods of interpretation or applying contemporary methods suggested by progressive Muslims. As this approach does not challenge the authority of the hadith, which is accepted culturally by majority of Muslims as second source after the Quran, cultural works for gender justice are assumed to be relatively more flexible and can be further maximized. By doing so, I argue that this cultural dimension of religion –accepting its sources and working on the field of interpreting them-should be considered in promoting gender justice among Indonesian Muslims.